Analysis and cost comparison of framed structure using different building materials under different load combinations. (2022) - Lakshmi Narayana, Jinka; Nikhil Vamsi, Gutti; Bhuvaneshwari, P.
Abstract: In the present study, the analysis and cost comparison of framed structures using different building materials under different load combinations were carried out. G + 7 storey framed structure of 24 m high was analysed for 8 load cases and 4 different load combinations. The bay width was maintained as 4 m in both directions (16 m × 16 m) and analysis was achieved through the licensed version of STAAD.Pro CONNECT V22. The material properties assigned were concrete, steel, and steel-concrete composite. The total cost of material utilised was calculated, with reference to the unit costs mentioned in the Standard schedule of rates. The cost comparison was carried out for each type of material under different load cases and different load combinations. It was observed that under extreme load combination, the concrete frame showed the increase in cost of 77%. Whereas the corresponding increase in steel-concrete composite frame and steel frame were 62% and 50% respectively. Even though the initial cost of steel structures is high, these structures were found to be optimal with less increment in cost under extreme load combinations.